2023
DOI: 10.2196/42677
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression With Precautionary Behavior Compliance, COVID-19 Fear, and Health Behaviors in South Korea: National Cross-sectional Study

Abstract: Background As of January 2022, the number of people infected with COVID-19 worldwide has exceeded 350 million. As the COVID-19 pandemic continues, people are affected in a wide range of areas of life, which in turn causes numerous psychological problems. Depression is a serious problem for people who have suffered from COVID-19. Depression can worsen COVID-19 precautionary behavior compliance or the health behavior itself. In addition, these depressive symptoms may have different characteristics de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…All the independent variables were entered in the multivariable regression as they are all potentially associated with behavioral intentions. [18][19][20][21][22][23]25,26 The adjusted OR (AOR) and 95% CI were reported. All analyses were carried out using the SAS 9.4 software (SAS Institute).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the independent variables were entered in the multivariable regression as they are all potentially associated with behavioral intentions. [18][19][20][21][22][23]25,26 The adjusted OR (AOR) and 95% CI were reported. All analyses were carried out using the SAS 9.4 software (SAS Institute).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Furthermore, psychosocial factors were included based on the behavioral theories (e.g., the minority stress model and the self-regulation theory 23,24 ) and previous studies, which showed that negative mental health, such as internalized stigma and depression, were barriers to practicing healthy behaviors. 25,26 This study aimed to investigate behavioral intentions of selfisolation and informing close contacts after developing mpox-related symptoms among young men who have sex with men (YMSM) aged 18−29 in China. This young age group was selected as they are more likely to report sexual risk behavior among MSM communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression symptoms, such as anhedonia and loss of energy, caused some functional impairments 26 . A previous study reported that both men and women with more severe depression were more likely to violate precautionary health behaviors as their depression worsened 27 . People with depressive symptoms would be unable to change their daily behaviors to precautionary measures during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of poor diet quality, low physical activity, and greater alcohol intake, BMI, and smoking represents an important risk for severe COVID-19 [9], COVID-19 mortality [10], and chronic diseases during the postpandemic period [11]. Accumulating evidence shows that particular groups, such as women and younger individuals, were more susceptible to higher levels of stress and depression during the pandemic, possibly due to changes in home life among others [12][13][14][15]. These factors, combined with limited access to grocery shops [8], restaurants, and food banks, restricted budgets due to sudden unemployment, and changes in living arrangements may have affected how people modified their lifestyle during the pandemic [16,17].…”
Section: Introductionmentioning
confidence: 99%